Joanna Kic-Drgas / Violeta Jurkovič. Paths of purpose. A journey into LSP teacher development. Göttingen: V&R unipress. 2024. Pp. 150 - Jaszczyk-Grzyb, Magdalena (Glottodidactica, 2024)
Review: Joanna Kic-Drgas / Violeta Jurkovič. Paths of purpose. A journey into LSP teacher development. Göttingen: V&R unipress. 2024. Pp. 150